The Enduring Challenge of Naxalism in India: Roots, Realities, and Responses - Shanta Barman (Journal of Asian Social Science Research, 2025)
Naxalism remains one of India’s most pressing internal security challenges. Emerging from the Naxalbari uprising in 1967, it has developed into a multifaceted insurgency driven by radical ideology, entrenched socioeconomic inequalities, and governance failures. This study examines the historical roots, ideological underpinnings, geographic spread, and structural conditions sustaining the movement. It also evaluates state responses, including counterinsurgency operations, development programs, and attempts to address underlying grievances. Despite prolonged efforts, Naxalism continues to undermine India’s democratic institutions and socioeconomic stability by occupying the developmental vacuum in affected areas. While the state’s approach has been predominantly security-focused, recent initiatives—such as those in Andhra Pradesh—indicate a possible shift toward more inclusive strategies. This paper argues for a comprehensive national policy that integrates security, development, and political dialogue to achieve sustainable peace and avoid the consequences of excessive militarization.